Uses of pepsin for collagen and gelatin extraction from bigeye snapper (Priacanthus tayenus) skin - Sitthipong Nalinanon (Prince of Songkla University, 2006)
Thesis (M.Sc., Food Technology)--Prince of Songkla University, 2006